Combination of capillary GC, GC/MS and 13C-NMR for the characterization of the rhizome oil of Piper betle L. (Piperaceae) from Vietnam. Issue 2 (1997) - Thanh Thanh, Lê Lê; Dũng Dũng, Nguyên Xuân Nguyên Xuân; Bighelliand Bighelliand, Ange Ange; Casanova Casanova, Joseph Joseph; Leclercq Leclercq, Piet A. Piet A.
Abstract : The essential oil from the rhizomes of Piper betle L. (betel), collected around Hue, was obtained in 0.20% yield. The oil was examined by a combination of capillary GC and GC/MS. 13 C-NMR studies confirmed the structure assignments proposed by retention data and mass spectra of the components with a content higher than 1%. In some instances the structure elucidation based on GC and GC/MS data had to be corrected. More than forty constituents were found of which the major ones were α-cadinol (26.2%), δ-cadinene (11.7%), and about equal amounts of T-cadinol and T-muurolol (unseparated, together 20.7%). This study clearly illustrates the advantage of complementary identification techniques.